Efficiency of the banking sector in Poland compared to other countries in the region - Anna Filipek; Krzysztof Spirzewski (Journal of Banking and Financial Economics (JBFE), 2023)
The banking system is one of the most important components of the financial systems on which modern economies are largely based. The occurrence of instability in this area may lead to serious economic problems. Therefore, the interest of researchers in this area has been focused mainly on assessing the effectiveness and efficiency of the banking sector, which will allow for identifying possible areas for improvement. In this paper, we discuss the use of efficiency as one of the basic measures used to assess the functioning of the banking sector. The aim of this study is to examine the efficiency of the banking sector in Poland, and then to compare the obtained results with selected countries of the region in 2014-2018. The paper presents theoretical considerations in the field of the financial system, the banking system and the efficiency of entities. In the empirical part of the paper, we conducted our own research on the efficiency of the banking sector in Poland using the DEA (Data Envelopment Analysis) method. The results were compared with those obtained in selected countries in the region. The selected countries of the region are: Bulgaria, the Czech Republic, Estonia, Croatia, Hungary, Lithuania, Latvia, Romania and Slovakia.
Keywords: C14; G21; 330; banking sector; efficiency; financial system; DEA method